Recollection of former Randia species, recognition of a rheophytic species of the Philippine endemic Villaria (Octotropideae, Rubiaceae) - Alejandro, Grecebio Jonathan D.; Meve, Ulrich (Phytotaxa, 2016)
Randia lanceolata and R. stenophylla (Gardenieae, Rubiaceae) are found to be conspecific and here transferred to the Philippine endemic genus Villaria (Octotropideae), and the new combination is here proposed. Villaria lanceolata is distinct from the other six members of the genus in showing a rheophytic habit and possessing narrowly lanceolate leaves, red fruits when ripe and prominent parallel ridges along the fibrous exostesta cells. The new member of Villaria is here comprehensively described, illustrated and typified.